LOS MECANISMOS DE EFECTIVIDAD DE LAS DECISIONES JUDICIALES: UNA MIRADA A LAS MEDIDAS CAUTELARES (2016)
Decree 01 of 1984 which contained the previous Administrative Code , with regard to precautionary measures , referred only to the temporary suspension of administrative acts , which meant that they were just coming as it were challenging administrative acts; but they were banned in cases of direct actions such as repair, in which the legality of an administrative act is not controviertía .With the reform of Law 1437 of 2011 the full spectrum of application of the precautionary measures changes in the measure are not only possible in terms of administrative acts but against any mechanism of action of the Administration , as is sought protection of rights and the effectiveness of the administrative procedure through the sentence.